Discovery of covalent enzyme inhibitors using virtual docking of covalent fragments. Issue 1 (1st January 2019) - Chowdhury, Sandipan Roy; Kennedy, Steven; Zhu, Kai; Mishra, Rama; Chuong, Patrick; Nguyen, Alyssa-uyen; Kathman, Stefan G.; Statsyuk, Alexander V.
Graphical abstract: Highlights: Virtual docking of 1648 covalent fragments is performed. Covalent inhibitor of Cathepsin L is identified. Cathepsin L inhibitor did not inhibit USP8, Calpain I, Cathepsin B. Abstract: Here we present a virtual docking screen of 1648 commercially available covalent fragments, and identified covalent inhibitors of cysteine protease cathepsin L. These inhibitors did not inhibit closely related protease cathepsin B. Thus, we have established virtual docking of covalent fragments as an approach to discover covalent enzyme inhibitors.